Leadless pacemaker implantation quality: importance of the operator's experience. Issue 6 (3rd May 2020) - Haeberlin, Andreas; Kozhuharov, Nikola; Knecht, Sven; Tanner, Hildegard; Schaer, Beat; Noti, Fabian; Osswald, Stefan; Servatius, Helge; Baldinger, Samuel; Seiler, Jens; Lam, Anna; Mosher, Luke; et al.
Abstract: Aims: Leadless cardiac pacemaker (PM) implantation differs from conventional PM implantation. While the procedure has been considered safe, recent real-world data raised concerns about the learning curve of new operators and their implantation quality. The goal of this study was to investigate the influence of the first operator's experience on leadless PM implantation quality and procedural efficiency. Methods and results: We performed a bicentric analysis of all Micra TPS™ implantations in two large tertiary referral hospitals. We assessed both leadless PM implantation quality based on the absence of complications (requiring intervention or prolonged hospitalization), good electrical performance (pacing threshold ≤ 1.5 V/0.24 ms, R-wave amplitude > 5 mV), and acceptable fluoroscopy duration (<10 min) as well as procedural efficiency in relation to the operator's experience. Univariate and multivariate logistic regression analyses were performed to identify predictors for implantation quality and procedural efficiency. Leadless PM implantation was successful in 106/111 cases (95.5%). Three patients (2.7%) experienced acute complications (one cardiac tamponade, one femoral bleeding, one posture-related PM exit block). Multivariate analysis showed that implantation quality of more experienced first operators was higher [odds ratio 1.09 (95% confidence interval 1.00–1.19), P  = 0.05]. Procedural efficiency increased with operator experience as evidenced by an inverse correlation of procedure time, time to the first deployment, fluoroscopy time, and the number of procedures performed (all P  < 0.05). Conclusion: The operator's learning curve is a critical factor for leadless PM implantation quality and procedural efficiency.